Dimensões de governança no setor público: estudo das controladorias federal e estaduais brasileiras - Cavalcante, Mônica Clark Nunes (2011)
Public governance is related to the assurance of a more secure institutional environment in the public administration, based on transparent, fair and reliable relationships, which contribute to alleviate the informational asymmetry and, consequently, the conflicts of interest between society and the government. The control represents a dimension of governance, to the extent that is it’s role contribute to this more reliable environment. This research analyzes the characteristics of the governmental environment and the Brazilian federal and State comptrollerships, in view of the recommendations of international bodies about principles and practice of governance and control. Through bibliographic and documentary search and applying questionnaire answered by 22 out of 28 internal control agencies, search universe, was evidenced that (1) governments are conceptually aligned with the principles of transparency and accountability, pillars of governance; (2) the governmental environment institutional characteristics and the control agencies practices are only partly aligned with the recommendations. Among the control practices, internal control area was the one that presented higher level of observance to recommendations and the one referring to the external report had presented the lowest level of attendance, represented by the low compliance with the reports content and dissemination practices, in accordance with international bodies recommendations considered in this research. Considering the conceptual alignment with the governance principles-transparency and accountability, would be expected that the comptrollerships agencies were greater aligned with the practices concerning to the dissemination to the public the informations, through the reports, presenting the public management results, including the one referring to the risk management.